Room temperature conductive type metal oxide semiconductor gas sensors for NO2 detection - Zhang, Chao; Luo, Yifan; Xu, Jiaqiang; Debliquy, Marc (Sensors and actuators. A. Physical., 2019)
[Display omitted] Air pollution is nowadays a big issue regarding the health of human beings. Among the toxic gases emitted in the atmosphere, NO2 is the most problematic one and a lot of countries or cities want to monitor its concentration in order to be able to take measures to reduce it. Therefore, it is urgent to develop NO2 sensors with high performance, low power consumption and low cost. Several technologies have been developed for this purpose. A very popular technology is based on metal oxide semiconductor. The usual semiconductor gas sensors need to be operated at high temperature, but nowadays many efforts are put on metal oxide sensors that can work at room temperature. These sensors present many advantages: low power consumption, low manufacturing cost, as well as moderate stability and safety. However, due to the weak response to NO2 at room temperature, most semiconductor NO2 sensors need to be adapted. This review will present the main strategies and material modification methods studied so far. These include light illumination, sensitization with an organic, formation of heterojunctions, preparation of composites with 1D or 2D materials and an introduction of oxygen vacancies in high concentrations. The gas sensing mechanisms of these sensors are presented and discussed.